Performance Evaluation of Different Control Schemes using Various Tuning Methods - Kumar, Rajeev (My University, 2013)
A control system is a device, or set of devices, that manages, commands, directs or regulates the behavior of other device or system to achieve the desired result. Controller design and choosing a particular control configuration/scheme is an important task in a particular control application. Different control configurations/schemes are used in process control for the purpose of controlling a particular application. These are feedback, feedback plus feed forward, cascade and cascade plus feed forward. The objective of feed-forward control is to measure disturbances and compensate error before the controlled variable deviates from the set point. The combined feed forward plus feedback control, can significantly improve performance over simple feedback control whenever a major disturbance can be measured before it affects the process output. Cascade controllers have a distinct advantage over other kinds of controller due to its ability to combine both feedback and feed-forward controls. Combining cascade and feed forward control techniques facilitates additional improvement in control loop performance. For obtaining desired closed loop response different tuning methods have been used. Tuning of PID controller for first order, second order and third order process has been done using Cohen-Coon, Direct Synthesis, Ziegler Nichols, Relay Auto tuning, Modulus Optimum, and Computational Optimization methods. In this work the performance evaluation of different control schemes using various conventional tuning methods such as Ziegler Nichols, Relay auto tuning, Modulus Optimum, and Computational Optimization have been compared. PID controller tuning using Particle Swarm Optimization (PSO) has also been done in this dissertation. The performance comparison between the different methods has been done using the parameters such as rise time, settling time, peak time, overshoot and steady state error. The proposed schemes have been implemented using MATLAB 2011b.
ME, EIED
Keywords: PED Controller; ZN; RA; PSO